The effects of electronic device use on athlete performance and health: a systematic review - Ong, N. C. H.; Chua, J. H. E. (International Journal of Sport and Exercise Psychology, 2025)
Electronic device use is an indispensable part of modern society which can affect athlete life and performance. The current study provides the first attempt to systematically review the effects of electronic device use on athlete performance and health. PsycINFO, PsycARTICLES, SPORTDiscus, Web of Science databases were searched for studies that fulfilled the inclusion criteria. The search strategy identified 33 studies (26 quantitative and 7 qualitative) which fulfilled the inclusion criteria. The findings revealed that there was little to no effect of electronic device use on athlete sleep, though this finding was marred by certain limitations (e.g., small sample size, training camp setting). Electronic device use increased mental fatigue in athletes, and this had resultant effects on certain areas of sporting performance. There were preliminary indications that electronic device use could affect mental health and psychosocial outcomes (e.g., anxiety, team cohesion), but further research is required to verify this claim. The findings of the systematic review indicate that electronic device use has both negative (e.g., stress and distraction) and positive effects (e.g., social connection and relaxation). These insights are significant as they highlight that electronic device use is a "double-edged sword", and that athletes need to learn how to optimise their electronic device use to attain better performance and health outcomes for their lives. Future research should seek to devise interventions to educate athletes on the effects of electronic device use and equip them with practical strategies (e.g., setting limits, scheduling use) on how to engage in healthy and positive use.